Educação, indústria cultural e livro didático - Brisolla, Lívia Santos (2015)
This study aims to investigate the Portuguese alphabetization books since contents, images and activities. It assumes a presupposed statement that the didactic book plays an important role in the contemporary educational scenario in Brazil and Portugal, as an instrument that forms values, especially when balancing the tensions of political, cultural, educational, social and economic contexts. Considering these aspects, it is possible to establish an intrinsic relation between didactic books and cultural industry. The study is based upon the Critical Theory of Frankfurt, as Adorno, Horkheimer and Marcuse, besides other authors as Freitag, Bittencourt and Magalhães. The concepts that supported the study are: education, didactic books, cultural industry, merchandise, ideology and publicity. The questions to be answered in this study are: Which is the relation between cultural industry and didactic books? Which are possibilities, aiming the reflexive and critical thinking, for contents and activities since images? In what way the art and publicity images lead to enlightenment or to puzzlement of contents? The study shows, on the one hand, that visual content hardly contributes for critical thinking, and, on the other hand, it contributes to instigate another range of knowledge and perceptions, as an entrance door to the thinking activity. The analyses point out to a necessity of enlarging the comprehension of relation between images, contents and activities beyond themselves, in order to promote the human and cultural formation instead of cultural industry impositions. The didactic book, as a scholar instrument, should be problematized, as the lack of criticism reflects a pseudo formation condition, and, finally, its design has to be based upon an education conception faced to enlightenment and to emancipation in the Kantian way.